2006
DOI: 10.1111/j.1541-1338.2006.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Based Participatory Research as a Tool for Policy Change: A Case Study of the Southern California Environmental Justice Collaborative

Abstract: In 2000, a regional rule governing maximum individual cancer risk from stationary facilities in Southern California was dramatically altered, reducing allowable risk levels by 75%. This article uses a case study approach to explore the role of a community-based participatory research (CBPR) partnership, the Southern California Environmental Justice Collaborative, in producing research and helping spearhead policy advocacy leading to this policy change. It also highlights the role of the collaborative in helpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 10 publications
0
49
0
1
Order By: Relevance
“…The scientific analysis helped the group to mobilize broader groups and conduct an effective media campaign and lobbying. In the end, they were able to achieve a substantial victory in changing a regional rule regarding cancer risk (Petersen et al 2006). This case suggests that communities need not be full participants in scientific research in order to achieve environmental justice victories.…”
Section: Typologiesmentioning
confidence: 99%
“…The scientific analysis helped the group to mobilize broader groups and conduct an effective media campaign and lobbying. In the end, they were able to achieve a substantial victory in changing a regional rule regarding cancer risk (Petersen et al 2006). This case suggests that communities need not be full participants in scientific research in order to achieve environmental justice victories.…”
Section: Typologiesmentioning
confidence: 99%
“…4 Community-based participatory research is a collaborative effort that utilizes the strengths, resources, and relationships within communities to maximize the benefits of the research process through comprehensive and sustainable interventions to address identified needs. 42 The CBPR model is especially suited to the challenges and opportunities embedded in occupational health research with immigrant workers, and is particularly appropriate to Lawrence. 43 For several years, Lawrence residents, local government agencies, and community-based organizations have worked in collaboration to improve the physical environment, create jobs, foster economic development, and address the health of the community.…”
Section: Setting and Approachmentioning
confidence: 99%
“…A growing trend in this area is the community-based participatory research, which emphasizes "involving community members in identifying issues in need of investigation, collaborating in the conduct of the research, and translating research-based findings into action, including advocacy for policy level change" (Petersen et al, 2006, p: 339). Case study evaluation of some of these efforts, especially in California, suggests significant success in the ability of these community-academic partnerships to affect policy change that benefits public health (Petersen et al, 2006;Minkler et al, 2008). The drawback of these case study evaluations is the difficulty in separating the effect of the partnerships from other contextual factors that contribute to the policy change.…”
Section: Previous Researchmentioning
confidence: 99%